Agricultural Production in Eastern Europe: History, Current Status, and Prospects of the Development for Innovation - Garazha , O.; Cherneha , I.; Ulanchuk , V.; Skus , O.; Nepochatenko , O. (Science and Innovation, 2023)
Introduction. Agricultural production is a prerequisite for the economic development of the Eastern European countries, which ensures food security of the citizens in the conditions of constantly varying economic environment. Problem Statement. The main condition for the development of the agrarian sector is an established system of selling products at high prices. Therefore, its assessment requires in-depth analysis, with the need for organic and high-quality food products making this problem extremely urgent. Purpose. Studying the current status of agro-food production and food security in the countries of Eastern Europe and the needs in raw materials of interrelated industries of the national economy, which can become a driving force for the development of rural areas; assessing the investment attractiveness of the agricultural sector; and determining the prospects for the development of agro-food production in Eastern Europe. Material and Methods. In this research, we have used systematic approach, comparative analysis, generalization, synthesis and analysis. The sources are statistical reports of international institutions, government and private organizations, scholarly research publications of foreign and domestic researchers. Results. The five elements of agro-food production in Eastern Europe have been identified: availability of resources suitable for agriculture; transformation of land relations; the structure of gross production by branches of agriculture; development of organic agriculture; investment attractiveness of the studied countries. The challenges of the agricultural sector at the middle and lower levels of agriculture have been described. Conclusions. The key prospects for the development of agricultural production in Eastern Europe are: improvement of the agricultural land market, sale of agricultural products in European and international markets, development of innovation through the introduction of modern technologies of agricultural production, development of organic farming, enhancing interest of credit and banking sector in investment projects in the sphere of agricultural production.